Interaction of advanced scientific irrigation management (ASIM) with I-SCADA system for efficient and sustainable production of fiber on 10,360 hectares - Mohamed, Nabil, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
Efficient drip irrigation of 10,000,000 fast-growing Pacific Albus trees in the water-challenged environment of Easter Oregon, US; requires not only a massive and complex computerized water distribution system but also an efficient and economical methodology to manage and deliver the water to the trees. The Greenwood Resources Boardman Tree Farm (GWR BTF) achieves this by interacting its Advanced Scientific Irrigation Management (ASIM) program with its state-of-art Irrigation Supervisory Control and Data Acquisition (I-SCADA) system to achieve high irrigation and economical efficiencies. Also within this ASIM / I-SCADA system combination is an elaborate automated soil moisture sensing operation and an original and innovative methodology incorporating a customized Advance Hydraulic Balanced Irrigation Scheduling (AHBIS) program, which enables smooth and steady hydraulic operation of 101 pumps at 23 major pump stations. Additionally, the BTF I-SCADA system operates pivot irrigation on 1,930 hectares (4,770 ac) of very high-value agriculture crops, including organic crops. Boardman Tree Farm offers a show-case example where the latest technology and human ingenuity are utilized to drip irrigate vast areas of land, while at the same time minimizing the use of scarce water and energy resources and maintaining a sustainable and economical rate of fiber production for use in BioEnergy, Paper and Solid Wood production.
Meeting irrigation demands in a water-challenged environment
Advanced scientific irrigation management
Presented at Meeting irrigation demands in a water-challenged environment: SCADA and technology: tools to improve production: a USCID water management conference held on September 28 - October 1, 2010 in Fort Collins, Colorado.